Effects of hydrogen dilution on morphological, structural and optical properties of NiSi/SiC core-shell nanowires by hot wire chemical vapour deposition / Abtisam Hasan Hamood Al-Masoodi - Hamood Al-Masoodi, Abtisam Hasan (2015)

(untitled)
NiSi/SiC core-shell nanowires grown on Ni-coated silicon substrates by hot-wire chemical vapour deposition were studied. Nickel was used as a catalyst to induce the growth of these core-shell nanowires at different hydrogen dilutions varying from 20 to 99 %. These nanowires consisted of single crystalline NiSi and amorphous SiC as core and shell of the nanowires, respectively. Moreover, an increase in hydrogen dilution enhances the decomposition rate and therefore improve the gas phase reactions of SiC formation. The shell of the nanowires showed the presence of 3C-SiC nano-crystllites embedded within an amorphous matrix. However, further increase in hydrogen dilution up to 99 % suppresses the growth of the nanowires attributed to film growth condition of SiC. The presence of Si and SiC nano-crystallites embedded within an amorphous matrix exhibited a room temperature PL emission in the range of 400-900 nm. These nanowires appeared a very low reflectance in visible range. The effects of the hydrogen dilution on the morphological, structural and optical properties of these core-shell nanowires are discussed. Keywords: Core-shell nanowires; hydrogen dilution; Nickel silicides; phase transitions; SiC; HWCVD.